FACTORS CAUSING SPEAKING DIFFICULTY FACED BY THE ELEVENTH-GRADE STUDENTS OF SMK NEGERI 6 PALU - Maya, Nur; Manurung, Konder; Wahyudin, Wahyudin (Tadulako University, 2025)
This research aims to discover the factors causing speaking difficulty faced by the eleventh-grade students of SMK Negeri 6 Palu. The researcher used qualitative descriptive research. The population of this research was the eleventh-grade students of SMK Negeri 6 Palu. The sample of this research was 48 students of the eleventh-grade class hotel accommodation chosen by applying a purposive sampling technique. In collecting the data, the researcher used a questionnaire and group discussion. The questionnaire and group discussion data were analyzed statistically and descriptively. The researcher found that the factors causing students difficulty in speaking are internal factors and external factors. The internal factors are students' interest, motivation, and lack of confidence. The external factors are teachers' strategy, learning facilities and the environment. This research implies that the teacher builds students' interest and motivation and encourages and increases students' self-confidence. In addition, the teachers choose the best teaching method to keep their learners involved in speaking. In a social environment, people are encouraged to use Indonesian combined with English, even though only for several words. This is so that students are accustomed to using English. In learning facilities, the teacher and school always try to provide interesting media for students so students are more interested and excited when learning to speak.